The Terms Used For Woman's Veil In The Pre-Islamic (Jahili) Poetry: A Pragmatic Study - Shereefah Ibrahim Muhamad Bin Taleb (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
The present research intends to investigate the names used for the woman's veil in pre-Islamic poetry (Jahili Poetry) using a pragmatic method to determine the significance of those phrases, how they were passed down through the generations, and how they evolved. The study will be conducted along three axes: the pragmatic approach concept, the status of the veil among Arabs, and the presentation of specific terms and texts relevant to the veil, as well as a